Yakuwarigo and Style Shifting in the Anime Genjitsushugi Yuusha no Oukoku Saikenki - Adipura, R T; Arianingsih, A (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
In the variety of yakuwarigo types, there is what is called style shifting, where language and word usage can change depending on the situation of the conversation and the interlocutor. This study aims to discover how the use of style shifting of the second person pronoun kiden in the anime Genjitsushugi Yuusha no Oukoku Saikenki. The data is collected using listening and note-taking, focusing on the dialogue of each character who performs kiden style-shifting. The collected data is then classified into a factor that influences style-shifting. It can be concluded that kiden style shifting occurs when the speaker and the interlocutor have the same or equal status(degree).